EFL Students’ Preferences for E-learning Platform: A Case of Schoology and Google Classroom - Nur Hasanah Safei; Ija Narmalawati (AL LUGHAWIYAAT, 2021)
This study aims to investigate students’ preferences on the use of Schoology and Google Classroom as online platform in EFL classroom. The participants of this study consist of 20 students. The research method uses a qualitative approach with descriptive data analysis technique. The qualitative data obtained by administering questionnaire and students’ reflection based on learnability, visual design, and satisfaction category were analyzed qualitatively. Learnabilty revealed that Google Classroom is the easiest platform for student to use compared to Schoology, while in terms of visual design, it revealed that Google Classroom is more attractive design than Schoology as a result, in the level of satisfaction, students were more satisfied with the features of Google Classroom than the features of Schoology.Keywords: EFL Students, E-learning, Google Classroom, Schoology